Moving Beyond Black Education Spaces: The Five Dimensions of Affirmation in Black Trans Education Spaces in Higher Education (International Journal of Multidisciplinary Perspectives in Higher Education, 2024)
This study explores the multifaceted dimensions of Black Trans Education Spaces (BTES) within higher education, shedding light on the unique experiences, challenges, and transformative potential of these spaces for Black transgender students while acknowledging that some Black education spaces may perpetuate trans-antagonism due to a lack of awareness, understanding, or intentional inclusivity regarding anti-queer and anti-trans rhetoric. Drawing on a collection of 20 narratives from both current and former Black transgender students at U.S. 4-year colleges and universities, this research investigates the existence of BTES both within and outside traditional educational structures. Findings indicate five dimensions of BTES: community determination, community actualization, community efficacy, community sustainability, and community reliance. These dimensions encompass the empowerment, identity affirmation, and collective support that Black transgender students derive from BTES. The narratives reveal the essential role of BTES in meeting the basic needs of Black transgender students, sustaining shared common senses, providing spaces for retreat and empowerment, and nurturing communities of care. The implications of these findings emphasize the importance of recognizing and honoring BTES, fostering greater solidarity, and addressing intersecting oppressions faced by Black transgender students. While BTES play a crucial role in supporting these students, broader inclusivity and understanding are needed in all educational spaces to ensure that all Black transgender individuals can thrive within higher education.